Doris Howes Calloway: A Woman Who Changed Nutrition Around the World. Issue 2 (March 2022) - Butte, Nancy F.; King, Janet C.; Murphy, Suzanne P.; Yates, Allison A.; Kretsch, Molly J.; Blackburn, Mary L.
Abstract : At the beginning of her career after World War II, Doris Howes Calloway pushed forward into the rapidly expanding world of science and medicine and, for more than 50 years, focused her energies, abilities, and knowledge of foods, biochemistry, and physiology to advance the field of human nutrition as a science and to improve public health for all. She extended the importance of her research and thinking into contemporary social issues of poverty, disparity, diversity, and inequities of hunger and malnutrition. Dr Calloway was a product of her times, overcoming obstacles presented by the Great Depression, World War II, and male dominance in science. Throughout her career, she advocated for the training, hiring, and promotion of women and for racial/ethnic diversity among students and faculty. Her legacy is that of a humanitarian as well as of a stellar scientist, university administrator, leader, and mentor. Dr Calloway was a renowned human nutrition scientist revered by her colleagues and students. Her research interests were broad with a far-reaching impact. Her pioneering research helped to establish protein and energy requirements, and the interaction of nutrition and physical activity. Later, her research extended to food composition and food properties, altered needs during space flight, nutrient requirements of reproductive women, and essential amino acid, mineral, and folate requirements. She ventured outside the laboratory to investigate nutritional problems among Native American, migrant, and other underserved populations. Her visionary approach to research, community interventions, and mentoring led to science-based strategies to improve the nutritional status of vulnerable populations in Mexico, Egypt, and Kenya. The constant throughout Dr Calloway's research was the impact of nutrition on the health, performance, and well-being of the population. She was particularly concerned about the physiological consequences of food inadequacy among impoverished populations. Dr Calloway referred to this work as a "foray into the real-world nutrition problems." Her work addressed contemporary social issues related to food access and quality, including health disparities. At a time when many scientists were narrowly focused, Dr Calloway maintained a broad portfolio of inclusiveness in her research and its application. Twenty years after her death, Dr Calloway's work continues to influence global nutrition as a result of her pioneering research theories and techniques. The scope of her contributions to human nutrition reaches far beyond her own research, to the outstanding contributions made through her 33 graduate students and numerous postdoctoral fellows and visiting scientists. She passed on to this network of students not only her excellent research methods and their applications but also her personal values of rigor, objectivity, integrity, and human equality. Dr Calloway's students continue her legacy, and many are now recognized as major contributors in the research and application of nutrition theory and practice. This article is the first in a series of publications that focus on the areas of research that Dr Calloway conducted, the impact of her work at the time the findings were published, and the continued contributions to contemporary scientific discourse around human nutrition, dietetics, and public health.